(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2018)
The study assesses the implementation of reading activities in the public elementary schools of the Schools Division of the City of San Fernando, La Union. Specifically, it looks into the extent of the implementation of reading activities; the challenges in their implementation; and the strengths and weaknesses in the implementation of the reading activities. The study utilized the mixed approach using sequential explanatory research design with researcher-made questionnaire as the tool for gathering data. The population consisted of 26 reading coordinators from the public elementary schools of the Schools Division of the City of San Fernando, La Union. The data gathered were treated statistically using frequencies and weighted means. The findings were validated through Focus Grouped Discussion (FGD) with the 25 reading coordinators conducted in Ilocanos Elementary School last June 6, 2017. The study found that the reading activities were highly implemented. The school systems that support and nurture the implementation, professional development, and effective instructional tools were some of sources of the challenges in the implementation of the reading activities. Most of the reading activities were rated as strengths. It was concluded that the implementation of the reading activities improves the reading proficiency of the pupils. The researcher crafted a Revitalized Reading Activities Plan to further hone the pupils’ reading skills. and recommended that it should be adopted and implemented by the teachers of the public elementary schools in the Schools Division of the City of the San Fernando, La Union.